2015
DOI: 10.1007/s40090-015-0037-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and inhibition effect of new antipyrinyl derivatives on mild steel corrosion in acidic solution

Abstract: Newly antipyrinyl derivatives 4 and 5 were synthesized from the reaction of enaminonitrile 3 with 1-nitroso-2-naphthol and salicyaldehyde, respectively, and used to protect mild steel dissolution in 1.0 M HCl solutions using weight loss, potentiodynamic polarization, and electrochemical impedance spectroscopy measurements. It was shown that these inhibitors act as good corrosion inhibitors for mild steel protection. The inhibition efficiencies were attributed to the simple blocking effect by adsorption of inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Additionally, it has been found that as (CS) concentrations increase, the impedance spectrum diameter increases. This indicates that the charge transfer mechanism has been inhibited and con rms that the extract successfully inhibits corrosion of HCS in acidic solutions .The (%E Eis ) and (θ) are obtained from the (R ct ) as the following equation [24]: 2…”
Section: Pdp Testmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, it has been found that as (CS) concentrations increase, the impedance spectrum diameter increases. This indicates that the charge transfer mechanism has been inhibited and con rms that the extract successfully inhibits corrosion of HCS in acidic solutions .The (%E Eis ) and (θ) are obtained from the (R ct ) as the following equation [24]: 2…”
Section: Pdp Testmentioning
confidence: 93%
“…As can be seen, the shape of the impedance spectra is similar with and without the addition of (CS) extract, indicating that the nature of the corrosion reaction has not changed. However, the impedance spectra is not a perfect semicircle, which may be due to the frequency dispersion caused by the roughness and unevenness of the solid electrode surface [24]. Additionally, it has been found that as (CS) concentrations increase, the impedance spectrum diameter increases.…”
Section: Pdp Testmentioning
confidence: 99%
“…The energy gap Egap indicates the reactivity tendency of organics toward the metal surface [50]. Thus, Egap has been used to characterize the binding ability of organic compounds to the metal surface [51]. A good corrosion inhibitor behaves as a strong Lewis base, and the electronegativity value of inhibitors is an important parameter in terms of electron transfer between metal and inhibitor.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…The adsorption of organic inhibitor molecules from the aqueous solution can be considered as a quasi-substitution process between the organic compounds in the aqueous phase [Org (sol) ] and water molecules associated with the metallic surface [H 2 O (ads) ] as represented by the following equilibrium [33,34]:…”
Section: Adsorption Isothermmentioning
confidence: 99%